Delaktighet för välmående och överlevnad : Fallstudie om en organisation med ambition att tillvarata sin fulla potential - Berge, Torild (2013)
The SSAB management in Luleå believes that a satisfying environment for the employees is imperative for a well functioning and prosperous organization. In their attempts to achieve this, several tools are used, among them work participation. A new production system initiated in 2007, SSAB One, requires this sort of participation among employees. Investigating how three levels of executives accompanied by a coach at Luleå SSAB attempt to create an environment for work participation is part of this thesis’ scope. It further encompasses how employees perceive the possibility of work participation and how further improvements can be made to the professional environment. The method consists of an abductive approach. Empirical data was gathered by semi structured interviews with three executives on different levels and a survey was carried out in the production group directly under the leadership of the level three executive. Also, a coach responsible for implementing SSAB One was interviewed for facts about this new production system. Through a combination of theoretical and empirical standpoints, prior research, and the theoretical framework this thesis have emerged. The result shows that SSAB Luleå created conditions for work participation in a way that is well connected to established theory. The majority of employees perceived their opportunities to participate as highly recognized. The conditions for work participation are expected to further improve by continuing the chosen approach. Validerat; 20131120 (ysko)